2022
DOI: 10.3390/pathogens11111270
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey of Mosquito-Borne Arboviruses in Wild Birds from Important Migratory Hotspots in Romania

Abstract: In the context of climate change, globalization, and enhanced human traveling, arboviruses continue to represent a threat to public health. West Nile and Usutu viruses are mosquito-borne viruses belonging to the Flaviviridae family (Flavivirus genus) and members of the Japanese encephalitis virus serocomplex. Included in the Togaviridae family (Alphavirus genus), the Sindbis virus is also vectored by mosquitoes. In the present study, we aimed to analyze the presence of antibodies concerning the abovementioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Although urbanisation, habitat loss and modification are the leading cause of population decline in psittacine species [ 50 ], infectious viral agents, such as BFDV and PsAHV1, are considered a significant threat to the persistence of robust populations of many psittacine species and add to the cumulative risk factors for threatened taxa. Avian species are additionally vectors for various zoonotic RNA viruses, which can cause disease within infected birds and humans, including influenza viruses, West Nile virus and Usutu virus [ 46 , 51 ]. However, the screening of these pathogens was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although urbanisation, habitat loss and modification are the leading cause of population decline in psittacine species [ 50 ], infectious viral agents, such as BFDV and PsAHV1, are considered a significant threat to the persistence of robust populations of many psittacine species and add to the cumulative risk factors for threatened taxa. Avian species are additionally vectors for various zoonotic RNA viruses, which can cause disease within infected birds and humans, including influenza viruses, West Nile virus and Usutu virus [ 46 , 51 ]. However, the screening of these pathogens was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first sequence-based evidence of USUV circulation in our country. However, seroprevalence study showed the circulation of USUV in wild birds sampled in localities in Tulcea county, including Danube Delta Biosphere Reserve, and in Constanta county [ 16 ] ( Figure 1 ), but not in human population in other part of the country [ 17 ]. The sampling sites chosen for our four-year study were Danube Delta and Bucharest metropolitan area.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not find evidence of USUV circulation in mosquito vectors collected between 2012 and 2013 in Danube Delta, a latter seroprevalence study (2018–2019) documented the presence of USUV in wild birds sampled in the area, mainly belonging to Passeriformes and Bucerotiformes orders. Of note, the species presenting the highest seroprevalence in this study was the common blackbird [ 16 ]. However, the same study failed to detect USUV specific antibodies in birds sampled in Bucharest in the same period when the C. pipiens s.l.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations